Economic Behavior of the Chinese Community in Padangsidimpuan: Reviewed from an Islamic Economic Perspective - Lubis, Rini Hayati (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to analyze the economic behavior of the Chinese community in Padangsidimpuan City and review its conformity with Islamic economic principles. The Chinese community is known to have distinctive economic characteristics, such as a high work ethic, disciplined financial management, and a family-based business network system. In the perspective of Islamic economics, ideal economic behavior should be based on ethical values and avoid harmful economic practices. Through a qualitative approach with interview and observation techniques, this study found that the economic practices of the Chinese community in Padangsidimpuan are in line with Islamic values, such as the ability to see opportunities (fastabiqul khairat), consistency of service (istiqamah), and profit-taking rationally (maslahah). The results of this study conclude that there is a potential for integration between Chinese economic values and Islamic economic principles in creating an inclusive multicultural economic model. This research contributes to the development of Islamic economic theory in the context of plural society and the importance of cultural inclusivity in economic practice.